Novel Distance-Based Molecular Descriptors for Styrene Butadiene Rubber Structures - Chidambaram, Natarajan; Kamran, Muhammad; Balasubramanian, Deepa; Hameed, Shahzaib; Mehmood, Saba; Raza, Wasim; Khan, Aamir Hussain; Iqbal, Zainab (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
Styrene-butadiene rubber (SBR) is a general-purpose rubber produced from a copolymer of styrene and butadiene.  It is used largely in automobile and truck tires. In general, it is considered to be an abrasion-resistant replacement for natural rubber.  In this article, we compute a set of recently introduced distance-based topological descriptors namely, Zagreb connection indices and reformulated Zagreb connection indices for the SBR structures. Zagreb indices and Reformulated Zagreb indices  were applied to forecast numerous molecular properties through QSAR studies of boiling point, Molar volume and bioactivity. These indices offer a quick and effective measure of molecular complexity and features of their composition resulting in approximate molecular behavior.